Estudo reológico do efeito de diferentes espessantes no desempenho de tintas - Feijão, Guilherme Aguiar (2020)
The formulation of the paints has as components resin, solvent, pigment, and additives. The additives are present in the paints to confer specific properties, among them the rheological properties. Among the additives that are responsible for the rheological properties, the thickeners stand out. Thickening agents have the function of controlling the viscosity of the system to provide certain desirable characteristics for its application, such as good leveling and no sagging. The present work was studied with hydrophobically modified alkaline expandable emulsions (HASE), used in Sample 1 (0.70% HASE) and Sample 2 (0.58% HASE), and carboxymethylcellulose thickener (CMC) contained in Sample 3 (0.40% CMC) and Sample 4 (0.92% CMC). The samples were subjected to rheological analysis with the aid of a rheometer and a laboratory runoff test. Shear thinning behavior was observed in all paint samples, characterized by a decrease in viscosity due to increased shear, which is important for its good quality. Samples with higher amounts of thickener showed higher viscosity at a lower rate than the others, which may be associated with thickener interactions. The data obtained by the rheometer were adjusted to the Herschel-Bulkley model and its parameters were defined, with Sample 1 showing an unusual behavior. Samples 2, 3 and 4 showed good data fit to the mathematical model, with a correlation greater than 0.95. At the end, the laboratory runoff test was done based on an adaptation of the ASTM D4400 standard to observe the runoff of the paints, with Samples 1 and 4 being the ones that achieved the best characteristics.